Stance : sociolinguistic Perspectives - Jaffe, Alexandra M. (Alexandra Mystra), 1960- (New York ; Oxford : Oxford University Press, 2009)
Stancetaking is central to communication. This collected volume explores stancetaking as a sociolinguistic phenomenon, looking at how speakers use language to position themselves and others and exploring how speakers and writers make use of and sometimes transform the meaning of sociolinguistic variables in their acts of stance.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sociolinguistics; Language and languages -- Style; Social interaction; Dicourse analysis -- Social aspects